The impact of eco-friendly car characteristics and eco-friendly factors on perceived value, trust, and purchase intention - Liu, Yuan-Yuan; Kim, Ha-Kyun (Edelweiss Applied Science and Technology, 2025)
As global awareness of environmental protection has grown since the 1990s, eco-friendly vehicles have emerged as a critical focus in the automobile industry. The depletion of oil resources and rising fuel prices have further catalyzed interest in sustainable transportation options. This study aims to investigate how eco-friendly car characteristics (safety, price, technological advancement, and brand) and environmental factors (carbon neutrality and green ecological environment) influence consumers’ perceived value, trust, and purchase intention. Using quantitative methodology, we conducted an online survey with questions adapted from previous research and analyzed data using SPSS 27.0 and Smart PLS 4.0. Our findings reveal that safety, price, and technological advancement significantly impact perceived value, while safety, price, and brand significantly affect trust. Regarding environmental factors, carbon neutrality influences perceived value, while both carbon neutrality and green ecological environment significantly impact trust. Furthermore, perceived value positively influences trust, and both significantly affect purchase intention. These results provide valuable insights for automobile manufacturers, policymakers, and marketers to better understand consumer preferences in the eco-friendly vehicle market, supporting the transition to sustainable transportation as consumers increasingly diversify their decision-making processes toward environmentally conscious choices.